Interpersonal Communication On The Quality Of Spousal Relationship Of Tb Ro Patients - Span Of Treatment Period: Komunikasi Interpersonal Pada Kualitas Hubungan Suami Istri Pasien Tb Ro - Rentang Masa Pengobatan - Istiqomah Istiqomah (Universitas Muhammadiyah Sidoarjo, 2024)
Tuberculosis is an irresistible illness that can go after anybody. The focal point of this examination purposely took instances of TB RO, where TB cases have a longest term of around 2 years contrasted with normal TB with a treatment time of 6 or 9 months. Then, the scientist plans to figure out the relational correspondence among husband and spouse couples, what is the nature of relational correspondence in couples impacted by TB RO illness, on the grounds that the treatment period is long, the nature of the husband and wife relationship might be viewed as in a terrible condition or the other way around, so this examination centers around the quality, for example, receptiveness, compassion, strong demeanor, inspirational perspective and balance found in relational correspondence while as yet focusing on a humanistic viewpoint where the component of humanistic accentuation is a lot of thought about in this point of view. Highlights : Extended Treatment Impact: Investigates how the prolonged treatment duration of TB RO (up to 2 years) affects marital relationships, differing significantly from standard TB treatment timelines. Communication Quality: Focuses on key aspects of communication quality in couples, including openness, empathy, supportive attitudes, positivity, and equanimity, amidst the challenges posed by TB RO. Humanistic Approach: Emphasizes the importance of a humanistic perspective in understanding and addressing the psychological and emotional dimensions of coping with TB RO within marital dynamics. Keywords : interpersonal communication, relationship quality, husband - wife, TB - RO